ANALISIS PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN SEJARAH DI SMA NEGERI 2 PONTIANAK - Ariandi, Cici; Sulistyarini, Sulistyarini; Rahmatika, Ika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to know diversity in SMAN 2 Pontianak. There were variety tribes such, as Dayak, Melayu and Madura. The writer was interest the way the history teacher taught in such diversity at the school and from different tribes. The method of this research used qualitative descriptive. The subject of research was the studant and the teacher at SMAN 2 Pontianak. The tediniques of data collection are, observation, interview an document ardsive notes. The tools of data collection used interview guide, observation sheets, and document. The result showing is, in this school, the teachers and students respect each other. There is no mayority and minority between students from particular tribes in the class and the students respect their diverseness. In this situation, the students were learning how to respect and having tolerance attitude. The teacher implement a learning model that shows diversity on learning process. There are on diversity obstacles in history learning pocess. Keywords: History Learning, Multicultural Education